20. RESEARCHING ON THE HEPAPROTECTIVE EFFECT OF HSN LIQUID EXTRACT ON PATIENTS WITH ALCOHOLIC LIVER DISEASE (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the hepatoprotective effect of HSN liquid extract on patients with alcoholic liver diseaseMethods: Interventional research, clinical trial, pre-post treatment comparison on 30 patients diagnosed with Alcoholic Liver Disease, treated at the Traditional Medicine Hospital of the Ministry of Public SecurityResults: After 30 days of treatment, the AST value decreased from 210.98 ± 64.50 U/L to 87.22 ± 47.66 U/L, statistically significant with p < 0.05. The ALT value decreased from 86.05 ± 26.29 U/L to 43.06 ± 12.57U/L, statistically significant with p < 0.05. The GGT value decreased from 437.50 ± 172.46 U/L to 181.50 ± 123.07 U/L, statistically significant with p < 0.05. Before treatment, the proportion of patients with GGT > 200 U/L after treatment accounted for 96.7%, after treatment, the proportion of patients with GGT from 50 - 100 U/L accounted for 26.6%, 101 - 200 U/L accounted for 36.7% and from 200 -500 U/L accounted for 36.7%, p < 0.05. Serum albumin value increased from 38.92 ± 4.36 g/L to 40.51 ± 3.62 g/L, p < 0.05. Total Bilirubin value decreased from 34.06 ± 7.28 to 18.28 ± 4.36 µmol/L, statistically significant with p < 0.05. The prothrombin ratio increased from 86.74 ± 9.09 to 96.96 ± 2.92%, p < 0.05. The mean Maddrey score decreased from 7.14 ± 7.35 to -1.75 ± 3.30, the difference was statistically significant with p < 0.05Conclusion: HSN liquid extract has good effects on patients with alcoholic liver disease, through improving the indices of AST, ALT, GGT, albumin, bilirubin, prothrombin and Maddrey score.
Keywords: hepaprotective; HSN; traditional medicine